Răspuns :
[tex]f(x) = \dfrac{x}{2}+1\\ \\ f(\sqrt 3) +f(3\sqrt 3) = \Big(\dfrac{\sqrt 3}{2}+1\Big)+\Big(\dfrac{3\sqrt 3}{2}+1\Big) = \\ \\ = \dfrac{\sqrt 3+3\sqrt 3}{2}+2 = \dfrac{4\sqrt 3}{2}+2 = 2\sqrt 3+2 = 2\cdot \Big(\dfrac{2\sqrt 3}{2}+1\Big) = \\ \\ = 2f(2\sqrt 3)\quad (A)[/tex]
Răspuns:
Explicație pas cu pas:
2f(2[tex]\sqrt{3}[/tex])=2([tex]\frac{2\sqrt{3} }{2}[/tex]+1)
=2[tex]\sqrt{3}[/tex]+2
=2(1+[tex]\sqrt{3}[/tex])
f([tex]\sqrt{3}[/tex])+f(3[tex]\sqrt{3}[/tex])=[tex]\frac{\sqrt{3} }{2}[/tex]+1+[tex]\frac{3\sqrt{3} }{2}[/tex]+1
=[tex]\frac{4\sqrt{3} }{2}[/tex]+2
=2[tex]\sqrt{3}[/tex]+2
=2(1+[tex]\sqrt{3}[/tex])
Deci da...Se verifica egalitatea